Wenckebach phenomenon in the exit area from a transvenous pacing electrode. Issue 2 (February 1976) - Peter, T; Harper, R; Hunt, D; Sloman, G
Abstract : An unusual type of exist block from a transvenous pacing electrode was recorded in a 63-year-old man with an acute inferior infarct and cardiogenic shock. The pacemaker artefact to QRS interval increased gradually till there was loss of capture. A gradual change from I:I pacing rhythm to 4:3 and 3:2 Wenckebach cycles was recorded. This was followed by a fixed 2:I pacemaker artefact to QRS block.